Index measured Impact on women’s empowerment and agriculture decision making in smallholder systems of South Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The agriculture based index has been created which enables to understand the behavioral approach of women towards adoption of climate smart practices. A synthesized report highlighting the results in form of publication will be soon updated for wider usage by the researchers and end-users.